The antimosquito properties of extracts from flowering plants in South Africa - Chalannavar, R.K. (2013)
Extracts of selected flowering plants, which are considered eco-friendly, are used for the treatment of numerous ailments and vector control worldwide. This has resulted in approximately 25 per cent of currently used drugs being derived from herbal sources. The aqueous and methanolic extracts of twelve plant species, Psidium guajava (pink fruit), Psidium guajava (white fruit), Psidium cattleianum var. cattleianum, Psidium guineense and Psidium X durbanensis, Achyranthes aspera, Alternanthera sessilis, Guilleminea densa, Capparis tomentosa, Leonotis leonurus, Dichrostachys cinerea and Carpobrotus dimidiatus, were tested for insecticidal activity, including larvicidal, adulticidal and repellent activities against the adult female mosquito, Anopheles arabiensis. The extracts of P. guajava (white fruit), C. tomentosa, L. leonurus,D. cinerea, and C. dimidiatus exerted a pronounced inhibitory effect on adult insects, while those of P. guajava (pink fruit), P. X durbanensis, P. cattleianum var. cattleianum, P. guineense, A. aspera, A. sessilis, and G. densa were ineffective and failed to satisfy the criteria set by the World Health Organization. In the tests for repellency against An. arabiensis, all the tested aqueous and methanolic plant extracts except those of A. sessilis repelled 80-100% of mosquitoes. The most effective mosquito repellents were the methanol and aqueous extracts of P. guajava (pink fruit), P. X durbanensis, P. cattleianum var. cattleianum, P. guineense, G. densa,L. leonurus and D. cinerea, which are potential sources of cost effective mosquito repellents to be utilized in malarial endemic areas.